Traumatic Memory and Family Dynamics of Political Prisoners in Leila S. Chudori’s Namaku Alam - Karim, Ahmad Abdul; Putra, Natanael Ricky; Amiruddin, Nurlina; Handoko, Agung Rizki Juwi; Ekklesia, Maylia Vinda; Vidyanita, Nissa (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
The violent aftermath of Indonesia’s 1965 political upheaval created profound, lasting trauma for politicalprisoners (tahanan politik, or tapol) and their families. This trauma continues to live within family memories,trapped in narratives of violence, oppression, and alienation. Leila S. Chudori’s novel, Namaku Alam, providesa compelling literary examination of this legacy, portraying how trauma transcends temporal boundaries andtransmits actively across generations. Through textual analysis grounded in trauma theory (Cathy Caruth)and concepts of intergenerational memory (Marianne Hirsch, Maurice Halbwachs), this article examinesthe psychosocial processes represented in the novel. The analysis reveals a three-stage progression: 1)family dynamics function as an arena for trauma transmission through silence, fragmented narratives,and somatic memory; 2) this transmission creates a distinctive inherited identity in the second generation,characterized by social stigma and psychological fragmentation; and 3) the legacy culminates in fracturedintergenerational relationships, where systemic violence manifests as domestic conflict and communicationbreakdown. This study reveals how Namaku Alam operates as a vital counter-narrative to official histories,serving as a bridge that illuminates the intimate, long-term consequences of state violence. By dissecting thefamilial mechanisms of trauma, the novel critiques the enduring impact of political repression on memory,identity, and relational life.